Wound Botulism Among Persons Who Inject Black Tar Heroin in New Mexico, 2016 - Middaugh, Nicole; Edwards, Leslie; Chatham-Stephens, Kevin; Arguello, D. Fermin (Frontiers in Public Health, 2021)
Outbreaks of wound botulism are rare, but clinicians and health departments should maintain suspicion for signs, symptoms, and risk factors of wound botulism among persons who inject drugs in order to initiate treatment quickly. This report describes an outbreak of three wound botulism cases among persons in two adjacent counties who injected drugs. Provisional information about these cases was previously published in the CDC National Botulism Surveillance Summary. All three cases in this outbreak were laboratory-confirmed, including one case with detection of botulinum toxin type A in a wound culture sample taken 43 days after last possible heroin exposure. Findings highlight the delay in diagnosis which led to prolonged hospitalization and the persistence of botulinum toxin in one patient.